2015
DOI: 10.1017/s1049023x15005282
|View full text |Cite
|
Sign up to set email alerts
|

Effect of First Aid Education on First Aid Knowledge and Skills of Commercial Drivers in South West Nigeria

Abstract: The training led to significant improvement in first aid knowledge and skills of intervention drivers. This confirms that lay responders can be trained in provision of first aid. The slight drop in skills scores, which occurred three months post-intervention, highlights the need for periodic refresher trainings to be conducted for the drivers in order to maintain the knowledge and skills acquired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 9 publications
(22 reference statements)
0
32
1
4
Order By: Relevance
“…Post-training surveys immediately after training and after six months showed that there was a significant improvement in first aid knowledge and skills confidence among traffic police. Similar studies on lay responder first aid training with participants other than police officers also demonstrated the positive impact of educational training on first aid knowledge and skills (9,10,(21)(22)(23). Common to these studies was the use of didactic and hands-on approaches to training.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Post-training surveys immediately after training and after six months showed that there was a significant improvement in first aid knowledge and skills confidence among traffic police. Similar studies on lay responder first aid training with participants other than police officers also demonstrated the positive impact of educational training on first aid knowledge and skills (9,10,(21)(22)(23). Common to these studies was the use of didactic and hands-on approaches to training.…”
Section: Discussionmentioning
confidence: 80%
“…Most RTI victims get to the hospital from the scene through the efforts of untrained civilians and medically unknowledgeable lay responders such as police officers (4)(5)(6)(7) The World Health Organization (WHO) recommends that where no prehospital trauma care system exists, first responder care should be established through the involvement of members of the community (8). Based on the WHO recommendation, several educational programs have been piloted across Africa to build knowledge and skills capacity of lay first responders to recognize an emergency, call for help, and provide initial care until formally trained health-care personnel can take responsibility (9)(10)(11)(12). Previous studies of educational programs have focused on drivers or a mix of participants.…”
Section: Introductionmentioning
confidence: 99%
“…Olumide et al 37 prospectively assessed knowledge retention after a first aid training program for truck drivers in Nigeria. Such a program has the potential to improve the care of road traffic accident victims in countries without developed EMS systems.…”
Section: Emergency Medicine Developmentmentioning
confidence: 99%
“…The World Health Organization (WHO) recommends that where no prehospital trauma care system exists, first responder care should be established through the involvement of members of the community [8]. Based on the WHO recommendation, several educational programs have been piloted across Africa to build knowledge and skills capacity of lay first responders to recognize an emergency, call for help, and provide initial care until formally trained health-care personnel can take responsibility [9][10][11][12]. Previous studies of educational programs have focused on drivers or a mix of participants.…”
Section: Introductionmentioning
confidence: 99%